Rolling Bearing Calculation with Deviated Components: Incorporating Geometrical Imperfections in the Layout Process of Rolling Bearing Assemblies - Kramer, Vincent; Wartzack, Sandro (Research in Tolerancing, 2024)
Rolling bearings range among the most important machine elements and are frequently deployed wherever rotating parts must be supported. Consequently, they are typically subject to a high number of load cycles, which may cause fatigue resulting in premature failure. The layout of bearings and their seats is therefore a crucial activity during the design of many mechanical systems such as transmissions. Bearing sizes must be chosen such that functional requirements (e.g., with regard to service life) are met while costs and weight are kept at bay at the same time. Within the state of the art, bearing calculations are regularly carried out based on the nominal shapes of the bearings and seat surfaces. However, real parts inevitably exhibit statistically distributed geometrical errors, which may cause changes of the load distribution within the bearings and thus affect vital quantities like fatigue life or operating clearance. This contribution presents a sampling-based method for the incorporation of deviated part geometries in the layout process of rolling bearing assemblies, enabling a more realistic calculation. The method is then demonstrated on an exemplary use case. Finally, remaining challenges are discussed and potential fields for future research are derive